Influence of Exponent in Damage Evolution Equation on the Accuracy of Damage Modelling in Brittle Materials - MIKA, Piotr (Engineering Transactions, 2015)
This paper analyses the influence of nonlinearity of the damage evolution equation that is introduced by exponent to the results obtained in the simulation of elastic-brittle material . Constitutive equation of linear-elastic medium with damages is described by the linear-tensorial function due to damage tensor. The nucleation and growth of microdamages are modelled using a two-parameter equation of damage evolution, in which the current level of damage is expressed by the principal values of Vakulenko-Kachanov and Murakami-Ohno damage tensors. The study examines a relationship between the time of the first macro crack appearance, principal values of damage tensor at the critical moment and the exponent adopted to the equation of damage evolution. The subjects of the analysis are changes in both the qualitative and quantitative variables characterizing the damage.